THERAPY-RELATED MYELOID MALIGNANCIES IN MYELOMA - Bart Barlogie; Xenofon Papanikolaou; Saad Usmani (Mediterranean Journal of Hematology and Infectious Diseases)
Therapy related myeloid malignancies are an increasingly recognized treatment complication in patients undergoing therapy for multiple myeloma. The main predisposing factors are the alkylating agents, topoisomerase II inhibitors and radiotherapy, but recently questions have been raised regarding the immunomodulatory agent lenalidomide. Little is known about the new antimyeloma agents in the context of therapy related myeloid malignanices. The duration of treatment and the time from diagnosis are the main contributing factors in alkylating induced myeloid malignancies which occur 5-10 years after treatment, chromosome 5 and 7 abnormalities being the characteristic finding. High dose therapy (HDT) does not seem to be a major contributing factor per se in multiple myeloma. In a number of large published series, all the factors related with therapy-induced myelodysplasia were defined prior to HDT. Topoisomerase II inhibitors induce mainly acute leukemias which invariably correlate with dysregulation of the MLL gene. Radiotherapy causes therapy related myelodysplasia if applied in bone marrow producing areas, especially if combined with chemotherapy. Therapy related myeloid malignancies generally herald a poor prognosis. Karyotypic abnormalities seem to be the main prognostic factor. In all cases the risk for therapy related myeloid malignancies drops sharply by 10 years after the treatment.